A Simple but Effective Combination of pH Indicators for Plant Tissue Culture - Funnekotter, Bryn; Mancera, Ricardo; Bunn, E. (MDPI, 2023)
The use of pH indicators provides a simple, semi-quantitative visual method for quickly assessing pH changes in tissue culture media; however, pH indicators are rarely used in routine plant tissue culture media. In this study, chlorophenol red, bromocresol purple, and bromocresol green were tested to assess their functionality in the growth medium for plant shoot cultures. In addition, a combination of bromocresol green and bromocresol purple was tested to determine if they would widen the observable colour change to better assess pH changes in the medium. Varying the ratio of bromocresol green to bromocresol purple alters the pH at which the colour changes from blue to green to yellow, with a 1:3 ratio providing a useful pH range of 5–6.5, while a 1:1 ratio provides a useful pH range of 4.5–6. All the pH indicators showed no toxic side effects for the plant species tested in this study and were able to be autoclaved to ensure media sterility. The addition of these pH indicators to quickly assess media pH in large tissue culture collections can aid in routine maintenance. These pH indicators can be used as a ‘traffic light’ system, with blue indicating a high pH, green a normal pH, and yellow a low pH in the media.